University continuing education and social change: Theoretical and methodological points of departure - Scott McLean; Bethany Beale; Silvana Romano (Adult Education Research Conference, 2006)
This paper explores the relationship between university continuing education and social change. It presents an example of how historical-comparative methods and sociological theory are essential for understanding this relationship.
Keywords: Universities; continuing education; social change; political economy